Application of the HeWuTong System in the Practice of the “River Chief System” - TAO Tao; ZENG Qingbin; HUANG Rong (Renmin Zhujiang)
HeWuTong application system is a modern information management platform built on the premise of fully integrating the needs of river management in the practice of “River Chief System” in Shenzhen.Through the system,the circulating water information resource base and multi-level linkage intelligent control platform shared by cities and districts are built with means of “system + responsibility + technology” and technologies of Internet of Things (IOT),GIS,big data,microservices,etc.;and a four-level “River Chief System”,regulatory system and technical system for the city,district,street and community are developed to realize the “full supervision,separated patrol and treatment,and intelligent management and control” of river channel in Shenzhen.HeWuTong system is the first intelligent management system for river patrol and management in China,which completely realizes the transformation from “River Chief System” to “river chief rule”,and plays innovative and demonstration role in the management of “River Chief System” in Guangdong Province and even the whole country.